Development of Competitiveness Model for Small-Medium Enterprises among the Creative Industry in Bandung - Utami, Ramadhilla Maghfira; Lantu, Donald Crestofel (The Indonesian Journal of Business Administration, 2013)
In Indonesia, Small-Medium Enterprises (SMEs) have a major role in term of generating employment, contributing to Gross Domestic Product (GDP), and being safety valve in national economic recovery. Nevertheless, nowadays the role of SMEs is not sufficient to promote the economic growth and to increase society income. It is difficult to SMEs to grow becoming larger business â€œnext stageâ€ or persist in sustainable productivity. This problem is considered related to the decreasing of SMEs competitiveness. This study aims to develop model of SMEsâ€™ competitiveness of creative industry cluster in Bandung. The research used intense theories that related to SMEs competitiveness. Based on preliminary study using existing researches, the competitiveness consists competitive abilities both internal and external factors and competing objects both financial and non-financial. This research also used theories on firm competitiveness: Porterâ€™s competitive strategy and competitive advantage model, the resource-based approach, and the strategic management approach. As a means to address its issue, it uses depth interview method using semi-structured interview. The data collection had three phases: preliminary phase, first phase, and second phase. Preliminary phase is conducted to test the questions. The first phase interview is conducted to some sub-sectors of creative industry cluster in Bandung that are included the SMEs criteria. Those are publishing and printing, computer software, culinary, crafts, fashion, interactive games, and performance art. Then, the data would be analyzed using grounded theory analysis in order to generate initial codes, sub-concepts, concepts, and categories. The second phase is conducted to validate the results of first phase and generate the final sub-concepts, concepts, categories, and finally build the theory. By knowing the concept of SMEsâ€™ competitiveness, the recommendation can be given related to development of creative industry cluster in Bandung. Competitiveness is viewed as a comprehensive concept. SMEsâ€™ competitiveness can be assessed from the influences up to the results achieved. Three dimensions that are included in competitiveness concept are potential dimension, process dimension, and performance dimension. Potential dimension consist factors that are needed to develop the business, started from owner characteristics and companyâ€™s characteristics that are influenced by internal capability and external environment. The second dimension named process dimension, which is consist effective operation strategy and implementation and effective growth strategy and implementation. The third dimension is performance dimension which is divided into financial performance and non-financial performance. The hypotheses related to model can be developed. Finally the recommendation based on previous analysis can be given to some entities such as business owner, government, and mediator institution in order to develop the SMEs.Â Key words: SMEs, Creative Industry, Competitiveness, Success Factor